The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1111/j.1365-2702.2008.02351.x
|View full text |Cite
|
Sign up to set email alerts
|

Value of wireless personal digital assistants for practice: perceptions of advanced practice nurses

Abstract: Nurses in this study support integrating wireless mobile computing technologies into their practice to improve client care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
39
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 36 publications
5
39
0
Order By: Relevance
“…There is a growing body of research on the incorporation of mobile devices in nursing practice as a communication tool and as a means of supporting evidence-based practice by providing access to information resources, practice guidelines, and drug information [10][11][12][13][14]. Doran (2010) investigated the impact of mobile devices on nurses' access to research evidence in Ontario, Canada, and reported that the most frequently used resources accessed by nurses included drug dictionaries and medical reference sources [11].…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…There is a growing body of research on the incorporation of mobile devices in nursing practice as a communication tool and as a means of supporting evidence-based practice by providing access to information resources, practice guidelines, and drug information [10][11][12][13][14]. Doran (2010) investigated the impact of mobile devices on nurses' access to research evidence in Ontario, Canada, and reported that the most frequently used resources accessed by nurses included drug dictionaries and medical reference sources [11].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Nurses felt that having access to devices changed their use of Registered Nurses Association of Ontario (RNAO) Best Practice Guidelines and that information resources assisted in their practice and improved patient care. In another study, nurses expressed the value of having clinical reference tools and drug information accessible on Personal Digital Assistants (PDAs) to their practice [12]. Mosbasheri reports more than half of nurses surveyed describe smartphones as very useful or useful.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Survey findings also indicate that cost may be a barrier for ICU nurses using personal PDAs at the bedside, a finding that is consistent with the literature. 19,24 ICU nurses are most interested in ICU-specific electronic references. Unlike school settings, where some students are required to purchase PDAs and specific programs for school and clinical use, most ICU nurses indicated hesitancy about purchasing (with their own resources) PDAs for clinical use.…”
Section: Discussionmentioning
confidence: 99%
“…A mistrust in technology and fear of a high workload associated with understanding and using innovative methods may have previously dissuaded front-line staff in primary care from embracing technology (Mannan et al, 2006). As many of the barriers that precluded the use of technologies are removed, health-care professionals now demonstrate an improved understanding of technologies and positive attitudes towards integrating technology into their practice based on an appreciation that there are distinct benefits to patient care (Garrett and Klein, 2008). The integration of technology into practice calls for an increase in IT and technology skills among the community nursing workforce, with education and training likely to be a critical factor in fostering the use of IT systems (Ward et al, 2008), encouraging familiarity, having faith in patients' desire or ability to adapt and allaying concerns about privacy and security.…”
mentioning
confidence: 99%